Western-centrism and contemporary Korean political thought - Jung In, Kang (Lexington Books, 2015)
An outgrowth of the critical examination of Western political theory embedded in Western-centrism and the tumultuous ideational processes by which contemporary Korean political theory and reality have intensely interacted (both in convergent and divergent ways). The book addresses complex and variegated ideas regarding Western centrism: the definition of Western-centrism; how Western-centrism is compared and contrasted with other forms of centrism such as Sinocentrism, capitalism (bourgeois-centrism) patriarchy (male-centrism), and racism (white-centrism); how Western-centrism has evolved in world history and in the history of Western political thought; how the evolution of contemporary Korean political thought has been interwoven with Western-centrism; the ill effects Western-centrism has brought about in Korean society and academia; and, ultimately, how Western-centrism can be overcome.